Day 3 Wed, November 15, 2017 2017
DOI: 10.2118/188601-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dissolution Effects on Dolomite Porous Media under Carbonated Water Injection CWI

Abstract: To investigate the effects of carbonated water injection (CWI) on dolomite porous media, a set of two coreflooding experiments were performed on outcrop samples. The results allowed the identification of the effects of dissolution on porosity and permeability on outcrop dolomite samples. Experiments were carried out at 70 °C, injection pressures of 8500 and 7500 psi, and a constant injection flow rate of 2 cm3/min. The experimental setup was assembled and commissioned arranging two coreholders connected in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
0
15
1
4
Order By: Relevance
“…This paper investigated the influence of CWI and WF on oil recovery improvement and induced formation damage in various low salinities. The result of CWI on permeability in sandstone media can be quite different from dolomite (observed by Nunez et al) (Nunez et al 2017). However, the following conclusion can be proposed from this study:…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…This paper investigated the influence of CWI and WF on oil recovery improvement and induced formation damage in various low salinities. The result of CWI on permeability in sandstone media can be quite different from dolomite (observed by Nunez et al) (Nunez et al 2017). However, the following conclusion can be proposed from this study:…”
Section: Resultscontrasting
confidence: 66%
“…They also concluded that acid solutions could be considered to work as a clay stabilising agent (Musharova et al 2012). Nunez et al reported some percentage increase in permeability during CWI in dolomite cores (Nunez et al 2017). In contrast to their investigation, permeability tends to decrease in the sandstone rock.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The studied rock's heterogeneity has an important effect on mineral dissolution, as Nunez et al 11 concluded. They reported that the mineral dissolution increases in the higher porosity region and decreases in the lower one.…”
Section: Mineral Dissolutionmentioning
confidence: 97%
“…Carbonated low salinity water (CLSW) is a combination of low salinity water and CO 2 (supercritical), coexisting in the same phase at p > 1072 psi and T > 87.8°F. 10,11 CLSW takes advantage of the high CO 2 solubility in the low salinity water (salting-in phenomenon), which ensures a high mass transfer of CO 2 from the CW to the oil, based on 3-7 times higher affinity of CO 2 to be dissolved in oil than in water. [3][4][5] CW had an enhanced sweep efficiency compared to the other CO 2 -EOR methods such as CO 2 injection and water-alternating-gas (WAG) due to oil viscosity reduction and CW's ability to overcome the shielding effect.…”
Section: Carbonated Low Salinity Water Floodingmentioning
confidence: 99%